2002
DOI: 10.1016/s0960-9822(02)00810-2
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans PAT-4/ILK Functions as an Adaptor Protein within Integrin Adhesion Complexes

Abstract: Our data strengthens the emerging view that ILK functions primarily as an adaptor protein within integrin adhesion complexes and identifies UNC-112 as a new ILK binding partner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
298
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(321 citation statements)
references
References 44 publications
20
298
0
3
Order By: Relevance
“…MIG-2 is a widely expressed and evolutionarily conserved FA protein (17)(18)(19)(20)(21). The experiments presented in this study have demonstrated a specific interaction between MIG-2 and the ␤1 and ␤3 integrin cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…MIG-2 is a widely expressed and evolutionarily conserved FA protein (17)(18)(19)(20)(21). The experiments presented in this study have demonstrated a specific interaction between MIG-2 and the ␤1 and ␤3 integrin cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 54%
“…MIG-2 (mitogen-inducible gene-2, also known as kindlin-2) is a widely expressed and evolutionarily conserved cytoplasmic protein (17)(18)(19)(20)(21). Genetic studies have shown that Caenorhabditis elegans UNC-112, a homolog of MIG-2, is required for attachment of body-wall muscle cells to the hypodermis (17,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these proteins have emerged as evolutionarily conserved mediators of integrin-actin linkages in muscle tissue. Together with the LIM-only adaptor protein PINCH and possibly Nck2, ILK and actopaxin are required for normal muscle development and integrinactin attachment in organisms as diverse as flies and worms (147,164,327). Although a role for paxillin in mammalian muscle cytoarchitecture is clear, the contribution played by this protein in lower organisms remains to be determined.…”
Section: Integrin-actin Linkages and Muscle Contractionmentioning
confidence: 99%
“…20 Interestingly, UNC-112 also interacts with the homolog of integrin-linked kinase or ILK. 21 In view of the similarity between this protein and MIG2, we have named this protein MIG2B. MIG2B was 52% identical and 76% homologous to MIG2 at the protein level.…”
Section: Identification and Characterization Of Mig2bmentioning
confidence: 99%